2012
DOI: 10.1007/s10741-012-9313-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic cardiomyopathy: pathophysiology and clinical features

Abstract: Since diabetic cardiomyopathy was first reported four decades ago, substantial information on its pathogenesis and clinical features has accumulated. In the heart, diabetes enhances fatty acid metabolism, suppresses glucose oxidation, and modifies intracellular signaling, leading to impairments in multiple steps of excitation–contraction coupling, inefficient energy production, and increased susceptibility to ischemia/reperfusion injury. Loss of normal microvessels and remodeling of the extracellular matrix ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
339
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(360 citation statements)
references
References 214 publications
(315 reference statements)
12
339
0
9
Order By: Relevance
“…Overall, 30 consecutive children and adolescents with type 1 diabetes (age range [5][6][7][8][9][10][11][12][13][14][15][16][17] years, male: 53%) were recruited at our pediatric endocrinology department and enrolled in this prospective cohort. Among children with diabetes, HBA 1c ranged from 6.8% to 12.7% , 63% of the patients with diabetes patients had HBA 1C > 8 % and mean diabetes duration was 5.1 ± 3.1 years.…”
Section: Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 30 consecutive children and adolescents with type 1 diabetes (age range [5][6][7][8][9][10][11][12][13][14][15][16][17] years, male: 53%) were recruited at our pediatric endocrinology department and enrolled in this prospective cohort. Among children with diabetes, HBA 1c ranged from 6.8% to 12.7% , 63% of the patients with diabetes patients had HBA 1C > 8 % and mean diabetes duration was 5.1 ± 3.1 years.…”
Section: Populationmentioning
confidence: 99%
“…Chronic hyperglycemia induces complex metabolic disturbances in cardiomyocytes, leading to morphological and functional abnormalities of the myocardium, grouped under the term "diabetic cardiomyopathy" [5] . Diabetic cardiomyopathy is characterized by the presence of extensive myocardial fibrosis, myocyte hypertrophy, increased oxidative stress, and microangiopathy [6] . While frequent, to date, a specific strategy for early detection or treatment of diabetic cardiomyopathy to improve its prognosis has not yet been established [6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The myocardium possesses an insulin receptor that determines its innate insulin signaling pathway connecting to metabolic 31) and mitochondrial remodeling [31][32][33] . It gains consensus that an abnormal excess of insulin signaling exerts vicious effects on the cardiovascular sys-induced impaired Ca 2 homeostasis 61) .…”
Section: Myocardial Hypertrophymentioning
confidence: 99%
“…However, it has been reported that lipid accumulation of cardiomyocytes changes their energy metabolism, increasing oxidative stress, impairing calcium handling and mitochondrial dysfunction, which promote cardiomyocyte death and interstitial fi brosis (Boudina and Abel, 2010). At present, clinical treatments for diabetic cardiomyopathy are aimed at delaying its progression, mainly by improving metabolic alterations using hypoglycemic agents, and cardiac performance using β-blockers and angiotensin-converting enzyme inhibitors (Miki et al, 2013). Therefore, new therapies intended to reverse heart failure in obese individuals would have a signifi cant impact on the health system (Bernardi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%